Fearless dominance and the U.S. presidency implications of psychopathic personality traits for successful and unsuccessful political leadership. [article]. - Lilienfeld, Kristin
Although psychopathic personality (psychopathy) is marked largely by maladaptive traits (e.g., poor impulse control, lack of guilt), some authors have conjectured that some features of this condition (e.g., fearlessness, interpersonal dominance) are adaptive in certain occupations, including leadership positions. We tested this hypothesis in the 42 U.S. presidents up to and including George W. Bush using (a) psychopathy trait estimates derived from personality data completed by historical experts on each president, (b) independent historical surveys of presidential leadership, and (c) largely or entirely objective indicators of presidential performance. Fearless Dominance, which reflects the boldness associated with psychopathy, was associated with better rated president performance, leadership, persuasiveness, crisis management, Congressional relations, and allied variables; it was also associated with several largely or entirely objective indicators of presidential performance, such as initiating new projects and being viewed as a world figure. Most of these associations survived statistical control for covariates, including intellectual brilliance, five factor model personality traits, and need for power. In contrasts, Impulsive Antisociality and related traits of psychopathy were generally unassociated with rated presidential performance, although they were linked to some largely or entirely objective indicators of negative job performance, including Congressional impeachment resolutions, tolerating unethical behavior in subordinates, and negative character. These findings indicate that the boldness associated with psychopathy is an important but heretofore neglected predictor of presidential performance, and suggest that certain features of psychopathy are tied to successful interpersonal behavior. -(from the author)
Keywords: Psychopathy; Antisocial behavior; Leadership; Politics; Personality